2004
DOI: 10.1124/mol.65.4.973
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Step Model of Prostaglandin Signal Termination: In Vitro Reconstitution with the Prostaglandin Transporter and Prostaglandin 15 Dehydrogenase

Abstract: Termination of prostaglandin (PG) signaling has been proposed to involve carrier-mediated uptake across the plasma membrane followed by cytoplasmic oxidation. Here, we tested this hypothesis directly by coexpressing the PG uptake carrier prostaglandin transporter (PGT) in various cell types with and without human PG 15 dehydrogenase (PG15DH). In HeLa cells, which express neither PGT nor PG15DH, exogenously added PGE2 or PGF2␣ were rapidly oxidized to the 13,14-dihydro,15-keto metabolites only when PGT and PG15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
102
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 32 publications
7
102
1
3
Order By: Relevance
“…CREB pathway leading to enhanced CYP19 transcription and increased aromatase activity (10). Extracellular PGE 2 can be transported via PGT into the cell, where it is inactivated by cytosolic 15-PGDH (24). Here, we show that changes in the levels of PGT modulate extracellular levels of PGE 2 , which lead, in turn, to changes in CYP19 transcription and aromatase activity.…”
Section: A B C D E F G H Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…CREB pathway leading to enhanced CYP19 transcription and increased aromatase activity (10). Extracellular PGE 2 can be transported via PGT into the cell, where it is inactivated by cytosolic 15-PGDH (24). Here, we show that changes in the levels of PGT modulate extracellular levels of PGE 2 , which lead, in turn, to changes in CYP19 transcription and aromatase activity.…”
Section: A B C D E F G H Discussionmentioning
confidence: 81%
“…This transporter is a member of the organic anion superfamily of transporting polypeptides that contain 12-transmembrane spanning domains (22). PGT is rate limiting in the delivery of PGE 2 to cytosolic 15-PGDH, which results in its oxidation and inactivation (23,24). Although numerous studies have shown the significance of enzymes involved in the synthesis and catabolism of PGE 2 as determinants of CYP19 transcription and aromatase activity, the potential importance of PGT in regulating aromatase expression is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PGT mediates PGE 2 cellular uptake, which can be driven by an exchange of organic anions such as lactate . PGT-mediated PGE 2 uptake from the extracellular environment is an initial step for degradation of PGE 2 by 15-hydroxy PG dehydrogenase (PGDH) in the cytoplasm (Nomura et al 2004). Expression of PGT may be coordinately regulated with COXs (Bao et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of PGE 2 located in the tumor microenvironment has been suggested to occur by a two-step model (13). The first step is mediated by the prostaglandin transporter (PGT), which engages carrier-mediated membrane transport of prostaglandins, including PGE 2 , PGF 2α , and PGD 2 (14), from the extracellular milieu to the cytoplasm.…”
mentioning
confidence: 99%
“…This transporter belongs to the organic anion superfamily of transporting polypeptides that contain 12-transmembrane spanning domains and are coordinately regulated with COXs (15,16). The second step of PGE 2 inactivation occurs in the cytoplasm, where 15-hydroxyprostaglandin dehydrogenase (15-PGDH) catabolizes and thus inactivates PGE 2 (13,16). We have recently reported that the expression and activity of 15-PGDH is repressed in human colorectal cancers and Apc min mouse adenomas, resulting in decreased catabolism of PGE 2 (17,18).…”
mentioning
confidence: 99%